Proteomic characterization of adrenal gland embryonic development reveals early initiation of steroid metabolism and reduction of the retinoic acid pathway - Dihazi, Gry H (Proteome Sci, 2015)
BACKGROUND: Adrenal glands are essential endocrine organs composed of two embryological distinct tissues. Morphological changes during their development are well described, but less understood with regard to their molecular mechanisms. To identify proteins and pathways, which drive the initial steps of the specification of the endocrine function of the adrenal gland, rat’s adrenal glands were isolated at different embryonic days (E): E14, E16, E18, E19 and postnatal day 1 (P1). RESULTS: The alteration of the proteome during the stages E16, E19 and P1 was investigated by combining two dimensional gel electrophoresis and mass spectrometric analysis. Out of 594 excised protein spots, 464 spots were identified, resulting in 203 non-redundant proteins. The ontogenic classification of the identified proteins according to their molecular function resulted in 10 different categories, whereas the classification of their biological processes resulted in 19 different groups. This gives an insight into the complex mechanisms underlying adrenal gland development. Interestingly, the expression of retinoic acid pathway proteins was decreased during the development of the adrenal gland, suggesting that this pathway is only important at early stages. On the other hand, key proteins of the cholesterol synthesis increased their expression significantly at E19 revealing the initiation of the endocrine specialization of the adrenal glands. CONCLUSIONS: This study presents the first comprehensive wide proteome analysis of three different stages of embryonic adrenal gland development. The identified proteins, which were expressed in early stages of development, will shed light on the molecular mechanisms underlying embryonic development of the adrenal gland. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12953-015-0063-8) contains supplementary material, which is available to authorized users.